An Evaluation of Removal Trapping to Control Rodents Inside Homes in a Plague-Endemic Region of Rural Northwestern Uganda - Eisen, Rebecca J.; Atiku, Linda A.; Boegler, Karen A.; Mpanga, Joseph T.; Enscore, Russell E.; MacMillan, Katherine; Gage, Kenneth L. (Vector-Borne and Zoonotic Diseases, 2018)
Rodents pose a significant threat to human health, particularly in rural subsistence farming communities in Africa, where rodents threaten food security and serve as reservoirs of human pathogens, including the agents of plague, leptospirosis, murine typhus, rat-bite fever, Lassa fever, salmonellosis, and campylobacteriosis. Our study focused on the plague-endemic West Nile region of Uganda, where a majority of residents live in Uganda government-defined poverty, rely on subsistence farming for a living, and frequently experience incursions of rodents into their homes. In this study, we show that rodent removal was achieved in a median of 6 days of intensive lethal trapping with multiple trap types (range: 0–16 days). However, rodent abundance in 68.9% of homesteads returned to pretreatment levels within a median of 8 weeks (range 1–24 weeks), and at least a single rodent was captured in all homesteads by a median of 2 weeks (range 1–16 weeks) after removal efforts were terminated. Results were similar between homesteads that practiced rodent control whether or not their neighbors implemented similar strategies. Overall, intensive lethal trapping inside homes appears to be effective at reducing rodent abundance, but control was short lived after trapping ceased.
Keywords: Rattus rattus; Yersinia pestis; Plague; Rodent control; Rodent-borne diseases